Optimizing Brand Identity of MSME Products through Rebranding in Increasing Consumer Brand Awareness - Sutrisno Sutrisno; Maisa Azizah Asmara; Sri Purwati; Susanto Susanto; Rudy Rudy (Journal on Education, 2023)
To establish a powerful brand identity, MSMEs must examine a variety of factors, including the target market, rivals, and brand positioning. This will assist them in determining the most suitable brand name, logo, and slogan for their items. In order to achieve the research objective of rebranding the business identity of one of the micro, small, and medium-sized enterprises (MSMEs) coffee shops, the SWOT analysis method is used to analyze the needs of product rebranding so that it can accommodate the business's strengths, weaknesses, opportunities, and threats. Based on the results of the SWOT analysis, the research recommends redesigning the product, particularly in terms of logos, utilizing a simple and elegant logo concept that is easily recalled by consumers in order to increase brand awareness. application of a company's brand identity to items. The application of brand identity to company items so that it can be observed that the use of color and iconic business logos can be a characteristic of the business brand image aids customers in remembering business specifics and aids businesses in promoting brand awareness. In Figure 4, there are several examples of the application of business logos that can bolster the credibility of the logo as a brand identity for MSME business products and increase consumer brand awareness of MSME businesses, particularly in the products sold and the segmentation of MSMEs business businesses.